Manpower Planning of Assembly Line Part A005TG2991ZJ at PT. Mitsubishi Electric Automotive Indonesia, Jawa Barat - Chyntia Ramadina; Ineu Widaningsih Sosodoro (President University, 2016)
Uncertainty presents on cars market demands affect in arranging the production plan of each automotive industry. Achieve the exact number of actual demand is nearly impossible since the demand itself is uncertain. As the demand increase, additional operators are needed to increase the output and vice versa. Manpower planning is useful in controlling such problems. The output and number of operators needed can be estimated hence, fulfilling demand then become easier. PT. Mitsubishi Electric Automotive Indonesia shortened as MEAINA is an automotive company has an issue regarded its manpower planning. Manpower plan for alternator assembly line producing model A005TG2991ZJ currently has been limited. Besides, the estimation of manpower plan is pretty rough. In overcoming this problem, yamazumi chart and precedence diagram are used to support the arrangement of workstations which directly affect to the manpower plan. By using the two method, improvement in output and line balancing percentage is expected to be obtained. The results confirmed that there is an improvement in the number of output, while line balancing percentage is slightly decline, nevertheless a significant improvement in both monthly output and line efficiency is detected on manpower plan of 20 operators.